SUPPLY CHAIN QUALITY MANAGEMENT (SCQM) PRACTICES AND THE EFFECTS ON CUSTOMERS' SATISFACTION IN THE BREWERY COMPANIES IN CAMEROON - Tiendem, Nicodemus; Messomo, Elle Serge; Molem, Sama C.; Mbu, Sunday Agbor (International Journal of Supply Chain Management, 2020)
Purpose: The heightening of competitive pressures has led companies to utilizing quality management practices through indirect competition. The brewery companies in Cameroon recently are noticing a wide variety of practices to this effect. This paper so sort to identify the supply chain quality management practices suitable for the brewery companies in Cameroon and also to examine their effects on customer satisfaction. Methodology: The study made use of a case study survey research design. The quest for originality and the desire to address issues particular to the brewery companies in Cameroon gave room for the use of primary data collected using a survey questionnaire. From a diverse population 200 customers of the four principal brewery companies in the South West Region participated in the study. The Cronbach's Alpha was used to identify key constructs of supply chain quality management while the OLS technique was used to examine their effects on customer satisfaction. Results: The study found that the supply chain quality management practice suitable for the brewery companies in Cameroon were top management commitment, strategic supplier partnerships, customer relationship management, information sharing and continuous improvement and innovation. Further, top management commitment, strategic supplier partnerships, customer relationship management, continuous improvement and strategic supplier partnership were found to significantly affect customer satisfaction at 5% level of significance while information sharing was insignificant. Generally, 39.9% of variations in customer satisfaction were as a result of changes in supply chain quality management. Unique contribution to theory, policy and practice: The unique contribution to practice rest on clearly identifying the constructs of supply chain quality management suitable to the brewery companies in Cameroon. In relation to theory the study established a significant relationship between supply chain quality management and customer satisfaction and made policy recommendations for the implementation of top management commitment, customer relationship management, continuous improvement and strategic supplier partnership.